2018
DOI: 10.1177/1833358318800459
|View full text |Cite
|
Sign up to set email alerts
|

Deploying unqualified personnel in health records practice: Role substitution or quackery? Implications for health services delivery in Nigeria

Abstract: Healthcare professionals are obliged to work collaboratively regardless of their professional differences in order to provide the highest possible standard of care to patients. However, this type of collaboration can also lead to role substitution and, in effect, engagement of unqualified personnel in all health professions, including the health information management profession. This is a particular problem in developing nations such as Nigeria, where this trend has the potential to undermine the delivery of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Though there are other factors responsible for variations in the level of education attained, health status along with socio-demographic factors play an important role as an unhealthy individual, a poor person and an old individual cannot attain the highest level of education which hinders productivity and economic growth in Nigeria. These findings corroborate discoveries of Adeleke et al (2019), and Brydges & Mkandawire (2018). Moreover, Adeleke, Suleiman-Abdul, Aliyu, Ishaq & Adio (2019) observed that collaborative works of health professionals might involve delegation and substitution of poorly qualified personnel which is a peculiar problem among less developed countries (LDCs).…”
Section: Discussionsupporting
confidence: 88%
“…Though there are other factors responsible for variations in the level of education attained, health status along with socio-demographic factors play an important role as an unhealthy individual, a poor person and an old individual cannot attain the highest level of education which hinders productivity and economic growth in Nigeria. These findings corroborate discoveries of Adeleke et al (2019), and Brydges & Mkandawire (2018). Moreover, Adeleke, Suleiman-Abdul, Aliyu, Ishaq & Adio (2019) observed that collaborative works of health professionals might involve delegation and substitution of poorly qualified personnel which is a peculiar problem among less developed countries (LDCs).…”
Section: Discussionsupporting
confidence: 88%
“…Role substitution and ‘de‐professionalisation’ is leading to the HIM profession being invisible (HIMAA, 2016). The potential impacts of role substitution include the mismanagement of health information systems, data errors, and privacy and confidentiality implications (Adeleke et al, 2019). These issues can lead to incomplete, inaccessible or incorrect information, thus impacting the clinician's decision making for patient care and ultimately, patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…Unqualified staff may not be aware of legislative and ethical requirements to protect health information to ensure privacy and confidentiality. Using unqualified staff to perform HIM professionals’ functions is a risk to patient safety (Adeleke et al, 2019). It is imperative that this profession endures and does not follow the same fate as Health Librarians with mixed opinions of the value they provide, from being seen as a financial burden (White, 2014) to an essential service to support clinical decision making (Taylor & Stephenson, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…2016) and equally high numbers are observed in other developing countries (Adeleke et al . 2019, Chandra and Bhattacharya 2019, Ecks and Basu 2009, Morgan et al . 2016, Naidu et al .…”
Section: The Context Of Practitioner Choices In Bholi Indiamentioning
confidence: 99%
“…In India and other developing countries, the space between affordable but unreliable public health system, and the more expensive formal private sector is occupied by IHPs (also called quacks, non-degree allopathic providers, unqualified private healthcare providers). Over 56 per cent of active healthcare workers in rural India are without formal qualifications or training (Rao et al 2016) and equally high numbers are observed in other developing countries (Adeleke et al 2019, Chandra and Bhattacharya 2019, Ecks and Basu 2009, Morgan et al 2016, Naidu et al 2003, Rao and Peters 2015, Rao et al 2016, Wahed et al 2010. These practitioners lack formal training and qualifications, tend to collect payments directly from users in cash or kind, and work outside the influence of regulatory bodies (Sudhinaraset et al 2013).…”
Section: The Context Of Practitioner Choices In Bholi Indiamentioning
confidence: 99%